Long-term effects of treatment of central precocious puberty with gonadotropin-releasing hormone analogs every three months. (1st December 2020) - Vatopoulou, Anastasia; Roos, Evelien; Daniilidis, Angelos; Dinas, Konstantinos
Abstract: Background: Gonadotropin-releasing hormone (GnRH) analogs represent the treatment of choice in patients with central precocious puberty (CPP). Recently, GnRH analogs that can be administered every 3 months have been developed and appear to be as safe and effective as one-monthly formulations. However, there are limited data regarding its long term safety and efficacy profile. We aimed to evaluate the long-term safety and efficacy treatment of CPP with GnRH analogs every 3 months. Methods: We prospectively studied all patients who were diagnosed with CPP in our center between January 2015 and December 2019. All patients were treated with intramuscular leuprolide acetate 11.25 mg every 3 months. Results: Twenty-four patients with CPP were included in the study. Mean follow-up was 3.1 years. Height gain ranged between 4 and 6 cm. Bone mineral density (BMD) was not affected. Body mass index (BMI) increased in all subjects but none was obese at the end of follow-up. Conclusions: Treatment of patients with CPP with GnRH analogs every 3 months induces substantial increases in height and does not affect BMI or BMD. Therefore, it represents an attractive option for these young patients.